Layanan Berbasis Lokasi Hotel Menggunakan Realitas Tertambah - Imansyah, Nur; Widiastuti, Sri Handani (JSINBIS (Jurnal Sistem Informasi Bisnis), 2017)
Getting information in real time at specific times and locations is especially needed when users have high mobility. But often users are not familiar with the area, so difficulty in finding locations and information. The development of technology for location based services and augmented reality makes it easy to get information from available resources in locations using mobile devices equipped with GPS devices. The research aims to combine hotel location based services and augmented reality in android-based mobile device by manipulating virtual objects into real objects through the camera as input and mobile phone display as output.The integration of hotel location based services and augmented reality is useful for hotel users to be able to search hotel information by directing the camera mobile device in the direction of specific targets to be retrieved information. The output of the system is provided in real time on the mobile device display for the user. Output information provided in the direction of location of the hotel object and information about the object of the hotel.Â